Ecotheology as a Framework for IPAS Learning to Build Human Relations with the Environment - Nurmala, Umi Ivayatuz Zulva; Susapti, Peni; Al-amin, Syafa Bachrun Naja (Dawuh Guru: Jurnal Pendidikan MI/SD, 2026)
This study aims to explore how eco-theology can be integrated into Natural and Social Sciences (IPAS) learning as a framework for fostering primary school students' understanding of the relationship between humans and the environment. Using a library research approach, this study reviewed various literature on environmental education, ecotheology, and science learning to identify patterns, conceptual trends, and the potential for integrating spiritual values into IPAS. The results of the study indicate that ecological relationships, context-based learning experiences, and the instilling of moral-spiritual values are important elements in effective environmental education. These findings were then analysed using Bronfenbrenner's Ecological Systems Theory and eco-theological principles to formulate an integrative model that connects ecological experiences across various student development systems with key eco-theological values, such as ecological monotheism, khilafah, amanah, and mīzān. The model emphasises that integrating ecotheology can shift IPAS learning from a purely cognitive focus to a more holistic, transformative learning process rich in ethical and spiritual values. This research provides a conceptual contribution to the development of ecotheology-based IPAS learning and offers practical guidance for teachers in designing learning that is relevant, contextual, and oriented towards strengthening long-term ecological awareness